MAPS development for the ALICE ITS upgrade - Yang, Ping; Aglieri, G.; Cavicchioli, C.; Chalmet, P. L.; Chanlek, N.; Collu, A.; Gao, C.; Hillemanns, H.; Huang, G.; Junique, A.; Kofarago, M.; Keil, M.; et al. (Journal of Instrumentation, 2015)
Monolithic Active Pixel Sensors (MAPS) offer the possibility to build pixel detectors and tracking layers with high spatial resolution and low material budget in commercial CMOS processes. Significant progress has been made in the field of MAPS in recent years, and they are now considered for the upgrades of the LHC experiments. This contribution will focus on MAPS detectors developed for the ALICE Inner Tracking System (ITS) upgrade and manufactured in the TowerJazz 180 nm CMOS imaging sensor process on wafers with a high resistivity epitaxial layer. Several sensor chip prototypes have been developed and produced to optimise both charge collection and readout circuitry. The chips have been characterised using electrical measurements, radioactive sources and particle beams. The tests indicate that the sensors satisfy the ALICE requirements and first prototypes with the final size of 1.5 × 3 cm2 have been produced in the first half of 2014. This contribution summarises the characterisation measurements and presents first results from the full-scale chips.
Gesehen am 10.07.2020